Experimental studies on the interactions between dolomite and SiO2-rich fluids: implications for the formation of carbonate reservoirs - Wang, Xiaolin; Wan, Ye; Hu, Wenxuan; You, Donghua; Cao, Jian; Zhu, Dongya; Li, Zhen (2017)
Objectives: Investigating the water-rock interaction mechanism and kinetics between dolomite and silica rich hydrothermal fluids; Discussing the effect of silica rich hydrothermal fluids on the formation of deep carbonate hydrocarbon reservoirs. Methods: Fused silica capillary tubes were used as reaction cells. Dolomite/calcite powder and deionized water were loaded into the fused silica capillary tube, which was made from pure silica. Thus, the silica involved in the water—rock interaction was from the dissolution of the tube; The vapor phase was in situ measured using a high resolution Raman spectroscopy (LabRAM HR800) with a spectral resolution of ~1 cm-1. The quenched solid products were analyzed using Raman spectroscopy, micro X ray diffraction (D/max Rapid II, Rigaku), field emission scanning electron microscope (Supra55, Zeiss) equipped with an energy dispersive spectrometer (Oxford Instruments, Inca X Max 150 mm Results: Dolomite can react with Si rich fluid to form talc, calcite and CO2 at temperatures above 100°C. The reaction can be described as: 3CaMg(CO3)2 + 4SiO2 + H2O = Mg3(Si4O10)(OH)2 + 3CaCO3 + 3CO2 The reaction was promoted by high temperature and/or lower partial pressure of CO2. In other words, high temperature and the presence of a conduit to release CO2 will promote the formation of talc; Talc and other Mg rich silicate minerals can be used to trace the activity of silica rich hydrothermal fluids in dolomite sequences. If silica originated from quartz/chert within the dolomite sequence, the hydrothermal alteration of dolomite by silica rich fluids would increase the porosity of dolomite reservoirs; In the Shuotuoguole area of Tarim Basin, silica rich hydrothermal fluids migrated upwards to the Yingshan Formation through deep faults. The interaction between the silica rich fluids and the Sinian-Cambrian dolomite would result in the formation of talc and CO2. Then, the produced CO2 ascends to the shallow limestone sequence of Yingshan Formation and promoted the dissolution of limestone to form large amounts of pores. The precipitation of micro quartz in the Yingshan Formation was favored by (a) decreasing temperature due to mixing between hydrothermal fluids and formation water, and (b) the presence of CO2. The results also support the view that the silica rich hydrothermal fluids responsible for the precipitation of micro quartz in the Shuntuoguole area were depleted in Mg.